Implication of STEAM Learning Model on Students' Scientific Creativity - Zakia Salsabila; Setiono; Jujun Ratnasari (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This research is motivated by the low level of students' scientific creativity in biology learning. The study aimed to examine the implications of the STEAM learning model on students' scientific creativity in the topic of water pollution. A quasi-experimental method with a non-equivalent control group design was applied, involving 60 grade X high school students divided into experimental and control classes. Data were collected through scientific creativity tests, observations, and student response questionnaires. The results showed a significant difference in posttest scores between the two groups (Sig. 0.000). The experimental class achieved an N-Gain of 0.74 (high category), while the control class scored 0.52 (medium category). Students’ responses toward the learning process were very positive, with an average score of 86.67%. These findings indicate that the STEAM model effectively enhances students' scientific creativity. STEAM learning not only improves students’ scientific creativity in specific contexts but also carries broader educational implications. This model can be adapted to various science topics and other subjects, strengthen interdisciplinary skills, and serve as a reference for curriculum development and teacher training. Thus, STEAM plays an important role in preparing students to face 21st-century learning challenges that emphasize creativity, collaboration, and problem-solving.